Validation of high frequency propagation prediction models over Africa - Tshisaphungo, Mpho (Rhodes University, Faculty of Science, Department of Physics, 2010)
The ionosphere is an important factor in high frequency (HF) radio propagation providing an opportunity to study ionospheric variability as well as the space weather conditions under which HF communication can take place. This thesis presents the validation of HF propagation conditions for the Ionospheric Communication Enhanced Profile Analysis and Circuit (ICEPAC) and Advanced Stand Alone Prediction System (ASAPS) models over Africa by comparing predictions with the measured data obtained from the International Beacon Project (IBP). Since these models were not developed using information on the African region, a more accurate HF propagation prediction tool is required. Two IBP transmitter stations are considered, Ruaraka, Kenya (1.24°S, 36.88°E) and Pretoria, South Africa (25.45°S, 28.10°E) with one beacon receiver station located in Hermanus, South Africa (34.27°S, 19.l2°E). The potential of these models in terms of HF propagation conditions is illustrated. An attempt to draw conclusions for future improvement of the models is also presented. Results show a low prediction accuracy for both ICEPAC and ASAPS models, although ICEPAC provided more accurate predictions for daily HF propagation conditions. This thesis suggests that the development of a new HF propagation prediction tool for the African region or the modification of one of the existing models to accommodate the African region, taking into account the importance of the African ionospheric region, should be considered as an option to ensure more accurate HF Propagation predictions over this region.
Keywords: Ionospheric radio wave propagation; Ionospheric radio wave propagation -- Forecasting; Radio meteorology; Radio wave propagation -- Africa; Ionosphere -- Africa -- Radio waves; Atmospheric physics -- Africa; Shortwave radio -- Africa